Weight self-misperception and obesity-related knowledge, attitudes, lifestyle behaviours and cardio-metabolic markers among Chinese school-aged children and adolescents - Jieyu Liu; Qi Ma; Xinxin Wang; Manman Chen; Tao Ma; Mengjie Cui; Jun Jiang; Yanhui Li; Di Gao; Ying Ma; Wen Yuan; Li Chen; et al. (Cambridge University Press, 2023)
Abstract Objective: The relationships between childhood weight self-misperception and obesity-related factors particularly health markers have not been extensively discussed. This study aims to examine the associations between weight self-misperception and obesity-related knowledge, attitudes, lifestyles and cardio-metabolic markers among Chinese paediatric population. Design: Cross-sectional study. Setting: Data sourced from a national survey in Chinese seven provinces in 2013. Participants: Children and adolescents aged 5-19 years. Results: Of the total 14 079 participants, there were 14·5 % and 2·2 % participants over-estimated and under-perceived their weight, respectively. Multi-variable logistic regression was applied to calculate OR and 95 % CI (95 % Cl) of obesity-related behaviours and cardio-metabolic markers by actual and perceived weight status. Individuals who perceived themselves as overweight/obese were more likely to have prolonged screen time, insufficient dairy intake and over sugar-sweetened beverages consumption (all P < 0·05), regardless of their weight. Furthermore, actual overweight/obese individuals had higher odds of abnormal cardio-metabolic markers, but a smaller magnitude of association was found among weight under-estimators. Among non-overweight/obese individuals, weight over-estimation was positively associated with abdominal obesity (OR: 10·49, 95 % CI: 7·45, 14·76), elevated blood pressure (OR: 1·30, 95 % CI: 1·12, 1·51) and dyslipidemia (OR: 1·43, 95 % CI: 1·29, 1·58). Conclusions: Weight over-perception was more prevalent than under-estimation, particularly in girls. Weight over-estimators tended to master better knowledge but behave more unhealthily; both weight over-perception and actual overweight/obesity status were associated with poorer cardio-metabolic markers. Future obesity intervention programmes should additionally pay attention to the population with inaccurate estimation of weight who were easily overlooked.